Willingness to Pay towards the Conservation of Ecotourism Resources at Gunung Gede Pangrango National Park, West Java, Indonesia - Nuva, R.; Shamsudin, Mad Nasir; Radam, Alias; Shuib, Ahmad (2009)
The objectives of this study are to determine the visitors’ willingness to pay for conservation of the resources at Gunung Gede Pangrango National Park (TNGP), and to determine the satisfaction of visitors towards the use of the ecotourism resources of the park. The dichotomous choice Contingent Valuation Method (CVM) was employed to determine the willingness to pay (WTP). A total of 423 respondents were interviewed face-to-face to collect the data. The results show that most visitors are satisfied with the ecotourism resources in TNGP, many of the visitors have come to TNGP more than once. In order to sustain the benefits derived from the resources at the park, the visitors agree that various organization involved must cooperate to conserve and protect the ecotourism resources. The economic benefit of conservation of the ecotourism resources at TNGP was measured using the visitors’ WTP for higher entrance fee to the park. A logit regression model was used to determine visitors’ willingness to pay. The results indicate that income, gender (male) and residential (urban) were the significant factors that influencing the visitors’ WTP for the entrance fee to TNGP. The mean WTP is found to be RP 7629.77 per visit. It is estimated that in 2004 the benefits of conservation of the ecotourism resources in TNGP amounts to RP 452 million.